Answer:
Step-by-step explanation:
From your problem statement, it seems you are asking to simplify the expression 2a with exponent negative 1 over 2.
So,
Considering the expression
[tex]\left(2a\right)^{-\frac{1}{2}}[/tex]
Lets simplify step by step
So,
[tex]\left(2a\right)^{-\frac{1}{2}}[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^{-b}=\frac{1}{a^b}[/tex]
[tex]\left(2a\right)^{-\frac{1}{2}}=\frac{1}{\left(2a\right)^{\frac{1}{2}}}[/tex]
[tex]=\frac{1}{\left(2a\right)^{\frac{1}{2}}}.....[A][/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \left(a\cdot \:b\right)^n=a^nb^n[/tex] on [tex]\left(2a\right)^{\frac{1}{2}}[/tex]
[tex]\left(2a\right)^{\frac{1}{2}}=2^{\frac{1}{2}}a^{\frac{1}{2}}[/tex]
So putting [tex]\left(2a\right)^{\frac{1}{2}}=2^{\frac{1}{2}}a^{\frac{1}{2}}[/tex] in equation [A]
[tex]=\frac{1}{\left(2a\right)^{\frac{1}{2}}}.....[A][/tex]
[tex]=\frac{1}{2^{\frac{1}{2}}a^{\frac{1}{2}}}[/tex] ∵ [tex]\left(2a\right)^{\frac{1}{2}}=2^{\frac{1}{2}}a^{\frac{1}{2}}[/tex]
Therefore, the simplified form of [tex]\left(2a\right)^{-\frac{1}{2}}[/tex] is [tex]\frac{1}{2^{\frac{1}{2}}a^{\frac{1}{2}}}[/tex]
Keywords: expression, simplification
Learn more about simplification of expression from brainly.com/question/13223583
#learnwithBrainly